Numerical investigations on tip leakage flow characteristics and vortex trajectory prediction model in centrifugal compressor. (December 2016) - Zhao, Huijing; Wang, Zhiheng; Ye, Shubo; Xi, Guang
To better understand the characteristics of tip leakage flow and interpret the correlation between flow instability and tip leakage flow, the flow in the tip region of a centrifugal impeller is investigated by using the Reynolds averaged Navier–Stokes solver technique. With the decrease of mass flow rate, both the tip leakage vortex trajectory and the mainflow/tip leakage flow interface are shifted towards upstream. The mainflow/tip leakage flow interface finally reaches the leading edge of main blade at the near-stall condition. A prediction model is proposed to track the tip leakage vortex trajectory. The blade loading at blade tip and the averaged streamwise velocity of main flow within tip clearance height are adopted to determine the tip leakage vortex trajectory in the proposed model. The coefficient k in Chen's model is found to be not a constant. Actually, it is correlated with h/b (the ratio of blade tip clearance height to blade tip thickness), because h/b will significantly influence the flow structure across the tip clearance. The effectiveness of the proposed prediction model is further demonstrated by tracking the tip leakage vortex trajectories in another three centrifugal impellers characterized with different h/b (s).